PERANCANGAN JARINGAN KOMUNIKASI VOIP (VOICE OVER INTERNET PROTOCOL) MENGGUNAKAN TRIXBOX PADA UNIVERSITAS ISLAM SUMATERA UTARA - Surya Hendra Putra; Oris Krianto Sulaiman (CESS (Journal of Computer Engineering, System and Science), 2019)
The use of communication media as a tool for activities and work at this time is very necessary, as for the technology used to support communication are PSTN (Public Switched Telephone Network), VoIP (Voice Over Internet Protocol) and so on. The Islamic University of North Sumatra uses PSTN communication media where the operational costs incurred by universities for communication media are quite large. VoIP (Voice Over Internet Protocol) is a technology that converts voice communication into a digital format that can be sent via LAN (Local Area Network) or the internet. VoIP requires a server for storing numbers or IDs used when communicating, Trixbox is a dedicated server operating system to handle VoIP using SIP (Session Initiation Protocol). This study aims to design a VoIP communication network so that using VoIP technology students, lecturers and employees in the Islamic University of North Sumatra can communicate with campus internet media without the need for telephone costs or data package fees or internet smartphone quotas to reduce expenses for operational costs university. Currently, the research is only in the Islamic University of North Sumatra campus environment, in the future it will be investigated how so that VoIP can be in the internet public network and how the security level of VoIP that is in the public internet.